2000
DOI: 10.1093/qjmed/93.7.449
|View full text |Cite
|
Sign up to set email alerts
|

High ethanol intake and malnutrition in alcoholic cerebellar shrinkage

Abstract: To determine the influence of chronic ethanol intake and nutritional status on cerebellar shrinkage in alcoholism, we studied 12 undernourished patients with acute Wernicke's encephalopathy (WE), 12 undernourished and 24 well-nourished asymptomatic chronic alcoholics, and 24 age-matched well-nourished controls, using morphometric analysis of MRI scans with volumetry of the cerebellum. Alcoholics reported a mean daily intake of ethanol of 177+/-8 g over a period of 27+/-1 years. Most undernourished alcoholics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
3
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 30 publications
2
28
3
1
Order By: Relevance
“…This finding is consistent with that in the previous literature 30,[39][40] that enhancement of mammillary bodies by contrast medium might be helpful to diagnose acute WE. However, it differs from the previous reports 34,[41][42] about alcoholic WE because the atrophy of the mammillary bodies and cerebellar vermis was not found during the acute stage and at follow-up of all patients in this study. The reasons leading to this difference have been explained in our previous report and may be the following: 6,38,43 The cerebellar vermis and mammillary bodies may be susceptible to thiamine deficiency in patients with alcoholism 2 ; these patients may have had previous attacks, and MR imaging findings in the acute phase of WE are contaminated by previous injury.…”
Section: Fig 3 Mr Imaging Images Demonstrating Cortical Damage In Pacontrasting
confidence: 99%
“…This finding is consistent with that in the previous literature 30,[39][40] that enhancement of mammillary bodies by contrast medium might be helpful to diagnose acute WE. However, it differs from the previous reports 34,[41][42] about alcoholic WE because the atrophy of the mammillary bodies and cerebellar vermis was not found during the acute stage and at follow-up of all patients in this study. The reasons leading to this difference have been explained in our previous report and may be the following: 6,38,43 The cerebellar vermis and mammillary bodies may be susceptible to thiamine deficiency in patients with alcoholism 2 ; these patients may have had previous attacks, and MR imaging findings in the acute phase of WE are contaminated by previous injury.…”
Section: Fig 3 Mr Imaging Images Demonstrating Cortical Damage In Pacontrasting
confidence: 99%
“…However, the prevalence of cerebellar atrophy as revealed MR imaging methods of the present study was only slightly lower (9.1 %) than those reported in previous CT studies (10-37 %) [16,34]. Somewhat disagreeing with the findings of the present study, a recent morphometric study showed vermal atrophy in 50 % of 36 patients with chronic alcohol consumption [27]. The planimetric method used in that study was very similar to those used in the present study.…”
Section: ■ Dentate Nuclei Intensity Does Not Correlate With Cerebellacontrasting
confidence: 86%
“…One reason for this difference might be an increase in brain volume during short-term abstinence in chronic alcohol-dependent patients [3,6,30]. In sum, it remains unclear why the prevalence of cerebellar atrophy found in the present study and previous CT studies differs so much from the high prevalence of 50 % reported by Nicolas et al [27]. A recently published study has shown that the ataxia in patients with uncomplicated alcoholism significantly and selectively correlated with white matter volume in the anterior superior vermis [38].…”
Section: ■ Dentate Nuclei Intensity Does Not Correlate With Cerebellacontrasting
confidence: 79%
See 1 more Smart Citation
“…This type of research confirmed and extended the results of post-mortem investigations. Enlarged ventricles (Hayakawa et al, 1992), wider cortical sulci (Estruch et al, 1997), as well as volume decreases of the corpus callosum (Nicolas et al, 2000), cerebellum (Sullivan et al, 2000) and subcortical structures like the hippocampus (Agartz et al, 1999), and caudate nucleus (Shear et al, 1992) have been reported.…”
Section: Introductionmentioning
confidence: 99%